KEBIJAKAN OTONOMI KHUSUS DI BIDANG PENGEMBANGAN SUMBER DAYA MANUSIA (Studi Perbandingan Beasiswa Provinsi Aceh dan Provinsi Papua) - Yuspani Asemki; Zahratul Idami; Mukhrijal (Pencerah Publishing, 2021)
The purpose of this research is to find out and explain the comparison of policies as well as to find out and explain the obstacles in the field of human resource development in Aceh Province and Papua Province. The method used in this research is descriptive qualitative research that produces comparative data. The theory used is the theory of decentralization, policy implementation, special autonomy, human resources and scholarships to answer these problems. The results showed that the Governments of Aceh and Papua carried out several programs to improve human resources. In the last four years, 2017-2020, the Aceh Provincial Government received 5,431 students with a budget allocation of Rp. 226,765,272,306. Meanwhile, the Papua Provincial Government accepts 8,125 students with a budget allocation of IDR 268,984,000,000 to develop the Human Resources (SDM) of Papua Province. The comparison in the last four years, the number of students in Papua Province is more than the Province of Aceh. While the results of the success and graduation of Aceh Province are clear in comparison to Papua Province with the reason that Aceh Province implemented the scholarship program first, while Papua only implemented it in 2013, the results are not yet clear. The obstacle for these two regions lies in the delay in communication and coordination between the government and BPSDM, so it is often late in informing the public and it is hoped that this program can be continued by the two regions. Communication and coordination between the government and BPSDM should be improved.